A Two-Photon Ratiometric Fluorescent Probe for Imaging of Hydrogen Peroxide Levels in Rat Organ Tissues - Lim, Chang Su; Cho, Myoung Ki; Park, Mi Yeon; Kim, Hwan Myung (ChemistryOpen, 2018)
Hydrogen peroxide (H2O2) is important in the regulation of a variety of biological processes and is involved in various diseases. Quantitative measurement of H2O2 levels at the subcellular level is important for understanding its positive and negative effects on biological processes. Herein, a two-photon ratiometric fluorescent probe (SHP-Cyto) with a boronate-based carbamate leaving group as the H2O2 reactive trigger and 6-(benzo[d]thiazol-2′-yl)-2-(N,N-dimethylamino) naphthalene (BTDAN) as the fluorophore was synthesized and examined for its ability to detect cytosolic H2O2 in situ. This probe, based on the specific reaction between boronate and H2O2, displayed a fluorescent color change (455 to 528 nm) in response to H2O2 in the presence of diverse reactive oxygen species in a physiological medium. In addition, ratiometric two-photon microscopy (TPM) images with SHP-Cyto revealed that H2O2 levels gradually increased from brain to kidney, skin, heart, lung, and then liver tissues. SHP-Cyto was successfully applied to the imaging of endogenously produced cytosolic H2O2 levels in live cells and various rat organs by using TPM.
Keywords: Biological process; Boronates; Fluorescent probes; Organ imaging; Rat organ imaging; Ratiometric; Ratiometric fluorescent probe; Two photon; Two photon microscopy; Two-photon probes; hydrogen peroxide; rat organ imaging; ratiometric fluorescent probe; two-photon microscopy; two-photon probe